A COMPARATIVE STUDY OF COMPLEX SENTENCE TRANSLATION IN ENGLISH USING GOOGLE TRANSLATE AND MICROSOFT TRANSLATOR - Palti Hansd Togi Maruhum Simanjuntak; Jonathan Hartodes Purba; Amos Frans Abdial Tarigan; Thamrin Daulat Dorianus Simanjuntak; Bloner Sinurat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of machine translation tools has revolutionized the way language barriers are overcome. However, the accuracy of these tools, particularly when translating complex sentence structures, remains a subject of interest. This study, compares the translation accuracy of two widely used tools, Google Translate and Microsoft Translator, focusing specifically on English complex sentences. The analysis evaluates their performance based on linguistic accuracy, syntactic structure preservation, and semantic clarity. Findings from this study, aim to provide insights into the strengths and limitations of these tools particularly on the translation accuracy for academic and professional translation purposes.